Characterization and Bio-Typing of Multidrug Resistance Plasmids From Uropathogenic Escherichia coli Isolated From Clinical Setting - Mukherjee, Sandip Kumar; Mukherjee, Mandira (Frontiers in Microbiology, 2019)
Urinary tract infection is primarily caused by Escherichia coli. Multidrug resistance and their rapid dissemination in this pathogenic microbe complicate therapeutic strategies and threaten public health. Conjugation systems responsible for interbacterial transmission of antibiotic resistance are plasmid-encoded and can be classified as the P, F, and I types. Specific pili types and pili associated proteins were related to the transfer among this gram-negative organism and were thought to depend on contacts created by these structures at the time of DNA transport. In this study, conjugation system types of the plasmids that harbour multidrug resistant genes (aac-1b-cr, oqxB, qnrB, qnrS, blaTEM, blaOXA) amongst 19 E. coli uropathogenic isolates were characterized under ciprofloxacin/ceftazidime selection individually by pili and pili associated gene types. Investigations indicated incidence of single plasmid of multiple replicon type amongst the transconjugants. blaTEM, blaCTX-M, blaOXA, aac-1b-cr, oqxB, qnrB, qnrS genes in varied combination were observed to be successfully co-transmitted against ceftazidme/ciprofloxacin selection. 7 primer pair sets were selected that encodes pili and pili associated genes (traF, trwJ, traE, trhE, traE, pilM, pilx4) by nucleotide database search tools using annotated plasmids of different incompatibility types to assign the conjugation system type of the transmissible resistant plasmids by PCR. traF was predominant irrespective of drug selection that indicated F-type conjugation system was responsible for transmission of resistant plasmids which results in the rapid dissemination of antibiotic resistance in the isolates screened. Therefore this is a first report of its kind that investigated pili and pili associated genes to bio-type multidrug resistant plasmids and their transmission in clinical settings amongst uropathogenic E. coli circulated in the eastern part of India.